2012
DOI: 10.1111/j.1468-1331.2012.03675.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency and mild cognitive impairment: cross‐sectional association

Abstract: Low 25OHD concentrations were associated with MCI status in older non-demented community-dwellers with subjective memory complaint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 39 publications
4
51
0
6
Order By: Relevance
“…Valuable, though limited in number, longitudinal studies indicated low levels of vitamin D were associated with substantial cognitive decline in the elderly population (Llewellyn et al 2010) and baseline vitamin D deficiency predicted the onset of non Alzheimer dementias (Annweiler et al 2012b). Importantly, Annweiler et al (2012a) showed the association of elevated serum 25OHD concentration with a lower risk of mild cognitive impairment (MCI) and the association of low 25OHD concentrations with MCI status in older non-demented people with subjective memory complaint, suggesting that hypovitaminosis D may participate in the dementia process from prodromal stages. Recent remarkable studies showed that vitamin D strongly stimulated phagocytosis and clearance of beta amyloid while protecting against apoptosis in AD patients' macrophages (Masoumi et al 2009;Mizwicki et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Valuable, though limited in number, longitudinal studies indicated low levels of vitamin D were associated with substantial cognitive decline in the elderly population (Llewellyn et al 2010) and baseline vitamin D deficiency predicted the onset of non Alzheimer dementias (Annweiler et al 2012b). Importantly, Annweiler et al (2012a) showed the association of elevated serum 25OHD concentration with a lower risk of mild cognitive impairment (MCI) and the association of low 25OHD concentrations with MCI status in older non-demented people with subjective memory complaint, suggesting that hypovitaminosis D may participate in the dementia process from prodromal stages. Recent remarkable studies showed that vitamin D strongly stimulated phagocytosis and clearance of beta amyloid while protecting against apoptosis in AD patients' macrophages (Masoumi et al 2009;Mizwicki et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The GAIT study is an observational cross-sectional study designed to examine gait in older community dwellers reporting subjective memory complaint. The sampling and data collection procedures have been described elsewhere [19]. In summary, subjective memory complaint was gathered using the Subjective Memory Complaints Questionnaire [20], and the main exclusion criteria were age <60 years, Mini-Mental State Examination (MMSE) score <10 [21], inability to walk independently, history of stroke, occurrence of any acute medical illness within the past 3 months, current delirium, severe depression, and inability to understand or answer the study questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Hypovitaminosis D is also highly associated with cognitive disorders, especially with advanced-stage dementia (8,9). Mild cognitive impairment (MCI) is the early stage of cognitive dysfunction, causing memory complaints without a disturbance in daily life activities, and is encountered with an increasing prevalence of AD (10). Although there are some studies examining the relationship between cognitive decline and vitamin D levels, to the best of our knowledge, it is not well documented and there is no consensus in the literature about the relationship between serum 25-hydroxyvitamin D level and patients' cognitive status.…”
Section: Introductionmentioning
confidence: 99%